Beyond internal conflict: The emergent practice of climate security. (January 2021) - Busby, Joshua W
The field of climate and security has matured over the past 15 years, moving from the margins of academic research and policy discussion to become a more prominent concern for the international community. The practice of climate and security has a broad set of concerns extending beyond climate change and armed conflict. Different national governments, international organizations, and forums have sought to mainstream climate security concerns emphasizing a variety of challenges, including the risks to military bases, existential risks to low-lying island countries, resource competition, humanitarian emergencies, shocks to food security, migration, transboundary water management, and the risks of unintended consequences from climate policies. Despite greater awareness of these risks, the field still lacks good insights about what to do with these concerns, particularly in 'fragile' states with low capacity and exclusive political institutions.